SOCIAL CAPITAL ON COMMUNITY DEVELOPMENT: SURVEY IN WEST JAVA INDONESIA - Dulkiah, Moh. (AKSELERASI: Jurnal Ilmiah Nasional, 2025)
This study analyzes the influence of social capital on community development, focusing on the role of university students in community service initiatives. Using a Systematic Literature Review (SLR) approach and Path Analysis, the VOSviewer analysis highlights that key concepts related to social capital, such as "community participation," "social trust," and "network building," frequently appear in relevant literature. These findings underscore the importance of these three dimensions of social capital in fostering community development. The VOSviewer software generated a visual map illustrating the interconnectedness of various topics, emphasizing that social network development and trust are prominent themes frequently discussed by researchers in the context of community development. The findings indicate the critical role of strengthening social capital in supporting effective collaboration and the sustainability of development programs. Following the SLR, Path Analysis was conducted to examine the relationships among variables in the model. The results reveal that Network (path coefficient: 0.496, T-statistic: 3.308, P-value: 0.001) and Trust (path coefficient: 0.463, T-statistic: 3.769, P-value: 0.000) have a positive and significant influence on Community Development. Conversely, Value (path coefficient: 0.019, T-statistic: 0.155, P-value: 0.877) shows no significant effect. These findings highlight the significant contributions of social networks and trust to community development, while social values within networks do not exert a notable impact. Based on these results, it is recommended that community service programs led by university students prioritize strengthening social networks and trust while promoting active collaboration. Furthermore, developing inclusive approaches to enhance social values within networks is essential. Future research is encouraged to explore additional factors influencing community development and the role of social values in sustaining these programs.